2015
DOI: 10.1016/j.bios.2014.10.036
|View full text |Cite
|
Sign up to set email alerts
|

A novel immunochromatographic system for easy-to-use detection of group 1 avian influenza viruses with acquired human-type receptor binding specificity

Abstract: A switch of viral hemagglutinin receptor binding specificity from bird-type α2,3- to human-type α2,6-linked sialic acid is necessary for an avian influenza virus to become a pandemic virus. In this study, an easy-to-use strip test to detect receptor binding specificity of influenza virus was developed. A biotinylated anti-hemagglutinin antibody that bound a broad range of group 1 influenza A viruses and latex-conjugated α2,3 (blue) and α2,6 (red) sialylglycopolymers were used in an immunochromatographic strip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…To investigate the effect(s) of the mutations on viral polymerase activity, we carried out minigenome assays of polymerases with these mutations in the genetic background of A/Vietnam/HN31432/2008 (VN/HN). VN/HN is a representative H5N1 clade 2.3.4 strain 27 with no known human adaptation mutations (e.g., PB2-E627K and PB2-D701N) in its HA and polymerase genes. VN/HN was used as the genetic background in this study because most of the identified mutations (13/24) were in clade 2.3.4, clade 2.3.4.1 or clade 2.3.4.3 viruses (Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the effect(s) of the mutations on viral polymerase activity, we carried out minigenome assays of polymerases with these mutations in the genetic background of A/Vietnam/HN31432/2008 (VN/HN). VN/HN is a representative H5N1 clade 2.3.4 strain 27 with no known human adaptation mutations (e.g., PB2-E627K and PB2-D701N) in its HA and polymerase genes. VN/HN was used as the genetic background in this study because most of the identified mutations (13/24) were in clade 2.3.4, clade 2.3.4.1 or clade 2.3.4.3 viruses (Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fumonisin B1, zearalenone, aflatoxin B1, deoxynivalenol (Oekanal standard solutions), polyethylene glycol (PEG, average mw 10 kDa), 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC), cadmium oxide (CdO, 99,99%), selenium powder (Se, 99,99%), sulfur powder (S, 99%), zinc acetate (Zn(OAc) 2 , 99,99%), oleic acid (90%), 1-octadecene (90%), oleylamine (70%), octadecylamine (90%), and trioctylphosphine, poly(maleic anhydride-alt-1-octadecene) (PMAO, M ~ 30 000-50 000) were obtained from Sigma-Aldrich (St. Louis, MO, USA). Tween 20, Triton X-100 and other chemicals were purchased from Merck-VWR (Milan, Italy).…”
Section: Reagentsmentioning
confidence: 99%
“…It was previously shown that oligosaccharide sequences do not affect the overall receptor stability [18,19]. Using sialic saccharides instead of antibodies to detect antigenic drift of influenza virus is promising [20]. Several groups have recently developed sensors based on sialic saccharides [21,22].…”
Section: Introductionmentioning
confidence: 99%